A105: Morphological characteristics and clinical significance of tumor infiltrating CD20 B lymphocytes in gastric cancer. Issue 1 (November 2015) - Tomchuk, O.
Abstract : The expression features of CD20 B-cells in gastric cancer (GC) are not well understood. The aim of the study was to give morphological characteristics of CD20 tumor infiltrating B-lymphocytes (TIL) and evaluate their clinical significance. We studied the samples of gastric mucosa (GM) adjacent to tumor in 35 patients with gastric cancer who had undergone radical surgery (R0) in Orenburg Regional Clinical Oncology Center between January 2009 and July 2010. The sections were stained immunohistochemically using antibodies to CD20. The density of CD20 B-lymphocytes was calculated using the relative area unit (RAU) equal to 0.42 × 0.28 mm 2 with the magnification×400. We observed 3 types of structures in which the expression of CD20 B lymphocytes was analyzed: individual cells located diffusely in the GM and the tumor stroma, focal lymphoid infiltrates (LI) and lymphoid follicles (LF). Cells expressing CD20 were of 2 types: round shape with sharp profile and a narrow rim of cytoplasm and irregularly shaped cells with indistinct contours and lots of cytoplasmic processes. There were 8 patients with atypical marked LF germinal center (AGC) arranged around the periphery of the follicle and irregularly shaped. AGC cells had large bright nucleus of round shape with distinct chromatin clumps and did not express CD20. Correlation between density of CD20 B-lymphocyte in GM and depth of tumor invasion (gamma = −0.474, p  = 0.01) and the number of lymph node metastases was found (gamma = −0.603, p  = 0.008). The lowest density value of CD20 B-lymphocytes was observed in three or more metastases (N2) in lymph node (56 + 19.5 + 30.3 + 16.4 and 26.9 + 16.1 cells per unit of area, respectively, with N0, N1 and N2, p  = 0.003) and depth of invasion G3-4 (55.7 + 19.7 and 32.8 + 19.7 cells per unit of area, respectively, for G1-2 and G3-4, p  = 0.02). In turn, the presence of focal LI correlated with the degree of differentiation (gamma = 0.525, p  = 0.02) and three-year overall survival (gamma = −0.738, p  = 0.03); the presence of LF correlated with the Grade (gamma = 0.525, p  = 0.02), histological type (gamma = 0.600, p  = 0.03) and the three-year relapse-free survival (gamma = −0.636, p  = 0.04); the presence of LF with AGC – with the Grade (gamma = −0.530, p  = 0.03), histological type (gamma = 0.726, p  = 0.02) and the degree of dysplasia GM (gamma = 0.833, p  = 0.001). Multiple LF, focal LI and LF with AGC bit more often observed at grade G3-4 and signet ring cell carcinoma (SRCC) (LF 0%, 25%, 42.9% and 55.6%, p  = 0.23, LI in50%, 42.9%, 100%, 66.7%, p  = 0.07 and LF with AGC 12.5%, 0%, 50%, 28.6%, p  = 0.17, respectively, when G1, G2, G3-4 and SRCC) and diffuse type gastric cancer (LF 20% and 50%, p  = 0.12 in 60% and 81.2%, p  = 0.23 and LF with AGC 10% and 41.2%, p  = 0.07, respectively, for the intestinal and diffuse type gastric cancer). Focal LI and LF with AGC were more common in moderate and severe dysplasia of the gastric epithelium (LI 58.3% and 84.6%, p  = 0.14 and LF with AGC 50%, 8.3%, p  = 0. 02). A decrease in the three-year relapse-free survival in multiple LF from 75% to 40%, p  = 0.04 and in the presence of focal LI – 83.3% to 57.9%, p  = 0.17 were observed. In the presence of focal LI, a decrease in the three-year overall survival from 100% to 73.7% was also observed ( p  = 0.14). The findings suggest that B-cells may be associated with the factors of GC progression. It is important that the high density of the diffuse B-lymphocytes was typical for early GC, whereas the presence of LI and multiple LF in GM adjacent to tumor was more often observed in diffuse type of GC, poorly differentiated tumors and signet ring cell carcinoma We believed, that further studies are needed for the understanding of the mechanisms whereby the B-cell LI and LF may be related with the histology type and Grade of GC.